Caracterização térmica de resíduos provenientes de usinas sucroalcooleiras para fins energéticos - Silva, Daniel Rodrigues da [UNESP] (2015)
This work presents the study of the main wastes produced by sugarcane mills such as bagasse, filter cake and vinasse in addition to thermal characterization for energy generation. Bagasse is obtained after juice extraction in the mills. Filter cake is generated after clarification of the juice for sugar production and used as an additive in mineral fertilizers on the sugarcane crops. Vinasse is a by-product of ethanol production obtained after distillation and is also applied on the crops as a fertilizer and to restore water to the soil. The samples of bagasse, filter cake and vinasse were provided by two sugarcane mills located in the state of São Paulo. Chemical composition of samples was determined by several techniques like ultimate analysis, FTIR spectroscopy, X-ray diffractometry, atomic absorption spectrophotometry among others. Thermal decomposition behavior of both pure samples and binary blends (1:1 w/w) was evaluated by thermogravimetric analysis and its derivative (TGA-DTG), differential thermal analysis (DTA) and differential scanning calorimetry (DSC). Typical reaction atmospheres of pyrolysis (N2), combustion (N2/O2, 8:2 v/v), oxy-combustion (CO2/O2, 8:2 v/v) and gasification (CO2) were employed. Thermal decomposition kinetics regarding the first mass loss step of degradation of organic matter was evaluated by Wanjun-Donghua method modified by Capela-Ribeiro. Results indicated that, despite similar organic composition, the energetic potential of filter cake and vinasse was lower than of bagasse due to increased inorganic content. Filter cake presented high amounts of Ca, Cu, Fe, Mn, P and Zn. Vinasse showed greater concentrations of Na and K and higher amounts of other metals such as Ca, Mg, Mn and Zn in relation to bagasse and filter cake samples. Both samples had significant concentrations of heavy metals like Cr and Pb. However, great differences were observed when chemical...